Attenuating lipid metabolism in atherosclerosis: The potential role of Anti-oxidative effects on low-density lipoprotein of herbal medicines - Huxinyue Duan; Pan Song; Ruolan Li; Hong Su; Lisha He (Frontiers Media S.A., 2023)
Atherosclerosis (AS) is a multifactorial chronic disease with great harm to the health of human being, which is a basic pathogenesis of many cardiovascular diseases and ultimately threatens human life. Abnormal blood lipid level is one of the most common diagnostic indicators of AS in clinic, and lipid metabolism disorder is often observed in patients with AS. Cholesterol is an important lipid in the human body, which is of great significance for maintaining normal life activities. Generally, cholesterol is transported to peripheral tissues by low-density lipoprotein (LDL), and then transported to the liver by high-density lipoprotein (HDL) via its cholesterol reverse transport function, and finally discharged. Under oxidative stress condition, LDL is commonly oxidized to the form ox-LDL, which is ingested by macrophages in large quantities and further forms foam cells, disrupting the normal metabolic process of cholesterol. Importantly, the foam cells are involved in forming atherosclerotic plaques, whose rupture may lead to ischemic heart disease or stroke. Furthermore, ox-LDL could also promote the development of AS by damaging vascular endothelium, promoting the migration and proliferation of smooth muscle cells, and activating platelets. Therefore, inhibiting LDL oxidation may be an effective way to improve lipid metabolism and prevent AS. In recent years, increasing studies have shown that herbal medicines have great potentiality in inhibiting LDL oxidation and reducing ox-LDL induced foam cell formation. Accordingly, this paper summarized current research on the inhibitory effects of herbal medicines against LDL oxidation and foam cell formation, and made a brief description of the role of cholesterol and LDL in lipid metabolism disorder and AS pathogenesis. Importantly, it is suggested that herbal medicines could inhibit LDL oxidation and regulate cholesterol homeostasis via downregulation of CD36 and SR-A, whereas upregulation of ABCA1 and ABCG1.